2018
DOI: 10.2478/ncr-2018-0011
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Production Parameters on Pozzolanic Reactivity of Calcined Clays

Abstract: Calcined clays are gaining increasing interest as future supplementary cementitious materials for the production of blended cements. Besides the mineralogy, the right production conditions can affect the pozzolanic activity of calcined clays. In this paper, the pozzolanic reactivity of two calcined natural clays in dependence of burning temperature, residence time in the furnace, cooling conditions and particle size of the final product is investigated. The highest pozzolanic reactivity was found at calcinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 15 publications
(20 reference statements)
0
21
0
3
Order By: Relevance
“…Danner and Justnes [18] investigated the pozzolanic reactivity of two calcined natural clays as depend on burning temperature, residence time in the furnace, cooling conditions and particle size of the final product. They found that the calcination temperatures of highest pozzolanic reactivity for both clays are between 600 and 800 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Danner and Justnes [18] investigated the pozzolanic reactivity of two calcined natural clays as depend on burning temperature, residence time in the furnace, cooling conditions and particle size of the final product. They found that the calcination temperatures of highest pozzolanic reactivity for both clays are between 600 and 800 °C.…”
Section: Introductionmentioning
confidence: 99%
“…The CC was used as a substitute for a certain fraction of the cement. The use of CC as a substitute for cement has various advantages, the main ones being that cement is the most expensive component of concretes, which production requires a large consumption of energy and the production of 1 ton of cement releases approximately the same amount of carbon dioxide into the atmosphere [1,[17][18][19][20][21][22][23][24][25][26]. Their properties, which include high early strength, low shrinkage, freeze-thaw resistance, and sulfate resistance, make them ideal for long-term S/S in surface disposal facilities.…”
Section: Introductionmentioning
confidence: 99%
“…The use of blended Portland-pozzolan cement results also in improved sustainability, sulfate resistance, and economic benefits [17][18][19][20][21][22][23][24][25]27]. By grinding the clay to a fineness greater than or equal to that of the cement (63 μm), followed by calcination at 720 °C, the clay becomes very reactive and has a high pozzolanicity [17,19,22,26]. The incorporation of a pozzolanic material in a cement mortar determines a chemical reaction in the presence of water between the amorphous SiO 2 of the pozzolanic material and the portlandite [Ca(OH) 2 ] released during hydration of the cement.…”
Section: Introductionmentioning
confidence: 99%
“…Bei der Flash-Calcinierung sind noch kürzere Calcinierungszeiten in der Größenordnung von wenigen Sekunden erforderlich. Ebenso wie die optimale Calcinierungszeit vom Calcinator abhängt, ist auch der Einfluss der Temperatur auf den Calcinierungsprozess bei unterschiedlichen Calcinator-Typen nicht übertragbar[7,9,26].Die Korngröße des Tons vor der Calcinierung ist aufgrund der in den Körnern auftretenden Temperaturgradienten ebenfalls ein wichtiger Parameter für den Calcinierungsprozess. Das Verhältnis von Volumen zu Oberfläche bestimmt die Kinetik des Calcinierungsprozesses, da die Reaktionen von der Gas-Feststoff-Grenzfläche nach innen fortschreiten.…”
unclassified
“…Für größere Körner sind demnach zum Durchcalcinieren längere Verweilzeiten erforderlich. Danner[9] und Chakchouk et al[27] stellten jedoch bei Versuchen zum Portlanditverbrauch bzw. Druckfestigkeitsprüfungen fest, dass längere Verweilzeiten auch die Reaktivität verringern können, selbst in einem Temperaturbereich, in dem keine Rekristallisation stattfindet.…”
unclassified